Procainamide and phenytoin. Comparative study of their antiarrhythmic effects at apparent therapeutic plasma levels. Issue 7 (July 1975) - Karlsson, E
Abstract : The antiarrhythmic effects of procainamide and phenytoin were studied in 81 patients admitted to the coronary care unit at the University Hospital in Linköping because of a suspected or proven diagnosis of acute myocardial infarction, and who developed ventricular arrhyhmias, requiring treatment, during the first 8 hours in hospital. Patients were randomly allocated to a procainamide of phenytoin group. The drugs were given as intravenous and oral loading doses followed by oral maintenance therapy. Plasma levels of the two druge were frequently determined and the electrocardiogram was continuously recorded during the 24-hour trial and analysed minute by minute. A significantly higher frequency of therapeutic failure was found in the phenytoin group (23 of 35 patients)compared to the procainamide group(13 of 39 aptients) during the first 2 hours after initiation of therapy. Four patients in the phenytoin group and 2 in the procainamide group developed symptoms probably caused by the trial drugs, necessitating discontinuation of therapy. The mean plasma levels were usually within the apparent therapeutic range (for phenytoin 40-72 mumol/l (10-18 mug/ml), and for procainamide 17-34 mumol/l (4-8 mug/ml). Seventeen patients (68%) in the phenytoin group and 10 patients (48%) in the procainamide group had plasma concentrations within this range when the therapeutic failure was observed. Nine patients died in hospital but only one of them during the trial. The results of this investigation clearly demonstrate the overall superiority of procainamide over phenytoin as an antiarrhythmic drug in short-term therapy after acute myocardial infarction.